2005
DOI: 10.18388/abp.2005_3469
|View full text |Cite
|
Sign up to set email alerts
|

The level of endogenous DNA damage in lymphocytes isolated from blood is associated with the fluctuation of 17beta-estradiol concentration in the follicular phase of healthy young women.

Abstract: The aim of this study was to evaluate whether the differences in plasma 17beta-estradiol concentration in early and late follicular phases of the menstrual cycle can affect the level of endogenous DNA damage in lymphocytes assessed by comet assay, and whether the extent of this damage in the follicular phase is associated with the genotype of catechol-O-methyltransferase (COMT). The level of DNA damage was positively correlated with 17beta-estradiol concentration only in the late follicular phase. Subjects wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Some studies have found non-significant differences, 24,48 whereas others have found a positive correlation between DNA damage levels (in the late follicular phase) and 17β-estradiol levels. 22 Furthermore, significant differences in DNA damage and repair among the menstrual cycle phases showed that the pre-ovulatory stage had the lowest DNA repair capacity. This variability in the observed results…”
Section: Phases Of the Menstrual Cycle Trimesters Of Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have found non-significant differences, 24,48 whereas others have found a positive correlation between DNA damage levels (in the late follicular phase) and 17β-estradiol levels. 22 Furthermore, significant differences in DNA damage and repair among the menstrual cycle phases showed that the pre-ovulatory stage had the lowest DNA repair capacity. This variability in the observed results…”
Section: Phases Of the Menstrual Cycle Trimesters Of Pregnancymentioning
confidence: 99%
“…21 DNA integrity is a critical homeostatic condition for survival and reproduction, in which DNA is the template for a new individual. In addition, DNA damage and repair levels are essential in reproductive processes, including the menstrual cycle [22][23][24] and pregnancy. 25 The detailed mechanisms that explain the association between ANA and the pathophysiology and development of SLE remain to be defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation